Bougie through Murphy’s Eye During Airway Exchange: A Near Miss - Sameera, Vattipalli; Biswas, Konish; Rath, Girija P. (Journal of Neuroanaesthesiology and Critical Care, 2020)
Endotracheal tube (ETT) exchange is a common procedure performed in the operating room and intensive care unit for the purpose of changing damaged or soiled ETT with appropriate one. The exchange procedure is performed over an airway exchange catheter or ETT introducer (bougie). We report an event during ETT exchange over bougie wherein the introducer exited through Murphy’s eye. Here, we intend to re-emphasize the safety concerns pertaining to the use of bougie (with coude tip) as airway exchange conduit and enumerate the precautions to be taken during tube exchange.
Keywords: endotracheal tube exchange; ETT introducer (bougie); Murphy’s eye; complications